Pengaruh Konsentrasi Pupuk Organik Cair Diperkaya Rhizobacteri Osmotoleran terhadap Pertumbuhan dan Hasil Tanaman Padi pada Kondisi Cekaman Kekeringan - Setiawan, Chandra Kurnia (Universitas Muhammadiyah Yogyakarta, 2016)
This study aimed to know the best concentration of Liquid Organic Fertilizer enriched Â with Rhizobacteri Osmotolerance to enhance plant growth and yield of rice in drought stress conditions. This research was conducted using single factor experiment arranged in a completely randomized design (RAL). The treatments tested are concentrations of POC 5 ml / l + NPK fertilizer 50% recommendations, POC concentration of 10 ml / l + NPK fertilizer 50% recommendations, POC concentration of 15 ml / l + NPK fertilizer 50% recommendations, POC concentration of 20 ml / l + NPK fertilizer 50% recommendations, and NPK fertilizer 100% recommendations with three replications. The results showed that Liquid Organic Fertilizer enriched with Osmotoleran Rhizobacter can reduce NPK fertilizers until 50%. Liquid Organic Fertilizer concentration of 15 ml / l + NPK fertilizers 50% tend to improve the growth and production of Ciherang rice in drought stress conditions.